ENHANCING THE SPEAKING SELF-CONFIDENCE THROUGH THE USE OF VLOG AMONG 11TH-GRADE STUDENTS AT MADRASAH ALIYAH ROUDLOTUL JADID IN LUMAJANG - Iman Wahyudi; Devy Wulandari; Sulistyaningsih Sulistyaningsih (Magister Scientiae, 2024)
Students in the eleventh grade at Madrasah Aliyah Roudlotul Jadid in Lumajang were the subjects of this study. The XI grade was chosen due to their self-confident in speaking were low. The purpose of this study was to demonstrate the pupils' improvement in self-confidence and to see the students’ perception in using VLOG to enhance their self-confident in speaking. The study was classified as classroom action research. This study used 4 (four) phases consist of planning, acting, observing and reflecting. Pre-cycle shows that 22 Student (73%) were under criteria of success (KKM) , and only 8 students (26%) have the criteria of success. The cycle 2 shows that 27 students (84%) have reached the criteria of success, only 3 students (16%) haven’t met the criteria of success. From the data collected, it shows that the students self-confident improved 58% compared to pre-cycle score. Moreover, students’ perception on using vlog in enhancing their self-confident through questionnaires was result positive. It is proven that VLOG can enhance the students self-confident in speaking and accepted positively by the students.